On the selection of culminating courses for outcome-based education evaluation at engineering education - Gunawan, Teddy Surya; Ismail, Md Yusof; Ihsan, Sany Izan (International Conference on E-Learning 2019, 2019)
In many engineering programmes in Malaysia, the tendency is to compute the Programme Outcomes (POs) attainment from first until last semesters for every student and each course. The average PO is then computed at the end of the semester/programme for each student/cohort. Weightages at the course and/or programme level are used to finalize the final POs achievement. However, it produces numbers which carries no significant meaning. An outcome is not a collection or average of previous learning experiences, but a manifestation of what learners can do once they have had and completed all of those experiences. The previous POs assessment at Kulliyyah of Engineering (KOE), IIUM, by measuring and averaging POs across courses is not supported by the current practice by ABET. PO or student outcomes in ABET terms are statements that describe what students are expected to know and be able to do by the time of graduation. Outcomes are high-quality ‘culminating’ demonstrations of significant learning in experiences, literally at the end or after the end. This paper presents the OBE framework at KOE-IIUM which categorize course into enabling and culminating courses, describes the process of selecting culminating courses from the engineering curriculum and provides a strategic POs evaluation for each culminating courses using rubrics.